Influence of electrochemically deposited polypyrrole layers on NiCo2O4-decorated carbon fiber paper electrodes for high-performance hybrid supercapacitor applications. (1st November 2019) - Ko, Tae Hoon; Kwak, Chae-Song; Seong, Jae-Gyoung; Cho, Young-Hun; Lei, Danyun; Choi, Woong-Ki; Kuk, Yun-Su; Seo, Min-Kang; Kim, Byoung-Suhk
Abstract: The electrochemically polypyrrole (PPy) layer deposited on NiCo2 O4 -decorated carbon fiber paper (PPy-NiCo2 O4 @CFP) composites was prepared by a consecutive two-step process. At first, the hierarchically NiCo2 O4 -decorated CFP (NiCo2 O4 @CFP) composite was prepared by a low temperature hydrothermal method. Secondly, the PPy layer was deposited onto the NiCo2 O4 @CFP composites using an electrochemical deposition method. The potential sweeping between −0.2 and 1.0 V was performed at a scan rate of 50 mV s −1 for various (0, 5, 10, 15 and 20) cycles in the presence of a pyrrole monomer. SEM images clearly indicated that the NiCo2 O4 nanostructures were uniformly grown over the CFP. Further, the PPy layer was also uniformly hierarchically-deposited over the NiCo2 O4 @CFP composites. The surface morphologies of the obtained PPy-NiCo2 O4 @CFP composites were dramatically changed depending on the electrodeposition cycles of PPy. We have prepared various PPy-NiCo2 O4 @CFP hybrid composites with different electrodeposition cycles of PPy layers, and the effects of electrodeposited PPy layers were investigated. The PPy-NiCo2 O4 @CFP composites with the 15 cycles electrodeposited PPy layers (PPy15-NiCo2 O4 @CFP//N-rGO@CFP) showed a maximum specific capacitance of 239 F g −1 at 2 A g −1 and excellent energy density of 64.95 Wh kg −1 at a power density of 1400.2 W kg −1 .